2021
DOI: 10.1016/j.ejca.2021.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 dose-escalation and pharmacokinetic study of regorafenib in paediatric patients with recurrent or refractory solid malignancies

Abstract: Background: This phase 1 study evaluated safety, pharmacokinetics (PK), maximum tolerated dose (MTD), and antitumour activity of regorafenib in paediatric patients with solid tumours. Patients and methods: Patients (aged 6 months to <18 years) with recurrent/refractory solid tumours received oral regorafenib once daily for 3 weeks on/1 week off. The starting dose (60 mg/m 2 ) was derived from an adult physiology-based PK model and scaled to children; dose escalation was followed by safety expansion of the MTD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 47 publications
2
21
0
1
Order By: Relevance
“…After screening, six additional clinical studies with results on clinicaltrials.gov were included in the analysis. In total, 70 records (64 published articles and 6 clinical trials with published results retrieved from clinicaltrials.gov) reporting AEs of anti-angiogenic drugs in pediatric patients with solid tumors were included in the systematic review [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After screening, six additional clinical studies with results on clinicaltrials.gov were included in the analysis. In total, 70 records (64 published articles and 6 clinical trials with published results retrieved from clinicaltrials.gov) reporting AEs of anti-angiogenic drugs in pediatric patients with solid tumors were included in the systematic review [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ,…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies evaluated AEs of anti-angiogenic drugs in patients with central nervous system tumors (sixteen various glioma [ 24 , 25 , 29 , 32 , 43 , 44 , 45 , 46 , 65 , 75 , 76 , 80 , 81 , 82 , 83 , 84 ], eight various brain tumors [ 28 , 33 , 54 , 59 , 61 , 64 , 72 , 88 ], three ependymoma [ 30 , 70 , 79 ], two medulloblastoma [ 23 , 51 ], one astrocytoma [ 47 ], and two neuroblastoma [ 56 , 78 ]). Twenty-three studies referred to a cohort of patients with various solid tumors [ 27 , 31 , 34 , 37 , 38 , 39 , 40 , 41 , 50 , 53 , 55 , 58 , 60 , 63 , 66 , 68 , 71 , 73 , 74 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regorafenib has been evaluated by the ITCC as single agent and subsequently in combination with chemotherapy in paediatric patients with recurrent or refractory solid malignancies (NCT02085148) [51]. It has been shown that regorafenib can be combined with standard dose vincristine and irinotecan in a sequential dosing schedule [52,53].…”
Section: Lessons From Soft Tissue Sarcomamentioning
confidence: 99%
“…Phase I studies on sorafenib, 14 everolimus, 15 or regorafenib 16 for pediatric relapsed or refractory solid tumors, including osteosarcoma, have been conducted, and the safety of these drugs in children has been established. Furthermore, a phase I/II study reported that lenvatinib has a median PFS of 3.0 months and an objective response rate of 6.7% 17 .…”
Section: Introductionmentioning
confidence: 99%